Detection and analysis of mangrove cover change in Kepalajerih Island, Batam, Indonesia using Landsat Imagery - AUNURRAHMAN AUNURRAHMAN; SUTRISNO ANGGORO; MAX RUDOLF MUSKANANFOLA; SURADI WIJAYA SAPUTRA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Aunurrahman, Anggoro S, Muskananfola MR, Saputra SW. 2023. Detection and analysis of mangrove cover change in Kepalajerih Island, Batam, Indonesia using Landsat Imagery. Biodiveritas 24: 6126-6133. For small islands, the mangrove ecosystem is crucial since it offers a variety of goods and services. In this study, we analysed the distribution and coverage of the mangrove ecosystem in Kepalajerih Island, Batam, Indonesia as well as the changes in mangrove ecosystem coverage over time. We also identified the required bands and their value range of Landsat data for mangrove detection. The research was carried out by applying reflectance selection to detect mangrove ecosystems. Landsat Imagery was used in the analysis, including Landsat 5 TM imagery of 1997 and Landsat 8 OLI imagery of 2015 and 2022. The result found that the combination of bands 1 and 5 of Landsat 5 TM or bands 2 and 6 of Landsat 8 OLI are applicable for mangrove detection. Reflectance of B1 or B2 less than 0.0325 indicates vegetation, while reflectance of B5 ranges from 0.0337 to 0.0837 or B6 ranges from 0.0454 to 0.0928, indicating wetland area. Therefore, the combination of both bands makes up for the mangrove area. Based on the analysis result, mangrove coverage in Kepalajerih Island fluctuated from 1,310.27 ha in 1997 to 1,117.29 ha in 2015 and then to 1,188.77 ha in 2022. The fluctuation was caused by a mangrove loss of as much as 262.17 ha and an expansion of 69.18 ha during 1997-2015, and a mangrove loss of 99.39 ha and an increase of 170.88 ha during 2015-2022. The natural drivers likely caused the fluctuation of mangrove coverage.